Bitumen and Bitumen Modification: A Review on Latest Advances - Michele Porto; Paolino Caputo; Valeria Loise; Shahin Eskandarsefat; Bagdat Teltayev; Cesare Oliviero Rossi (Applied Sciences, 2019)
This synthesis explores the state-of-the-knowledge and state-of-the-practice regarding the latest updates on polymer-modified bitumens (PmBs). The information in this study was gathered from a thorough review of the latest papers in the literatures related to modified bituminous materials, technologies, and advances. For this purpose, the paper is presented in two principle sections. In the first part, the bitumen itself is investigated in terms of chemical structure and microstructural systems. In the second part, the paper focuses on bitumen modification from different aspects for assessing the effectiveness of the introduced additives and polymers for enhancing the engineering properties of bitumen in both paving and industrial applications. In conclusion, the knowledge obtained in this study has revealed the importance of the chemical composition of base bitumen for its modification. It can be declared that while some polymers/additives can improve one or some aspects of neat bitumen properties, they can lead to compatibility problems in storage and production. In this respect, several studies showed the effectiveness of waxes for improving the compatibility of polymers with bitumen in addition to some benefits regarding warm mix asphalt (WMA) production.